Skin manifestations in children with inborn errors of immunity in a tertiary care hospital in Iran - Zahra Salehi Shahrbabaki; Zahra Chavoshzadeh; Fahimeh Abdollahimajd; Samin sharafian; Mahnaz Jamee; Anastasia Bondarenko; Tolue Mahdavi (Frontiers Media S.A., 2023)
Abstract Objectives Inborn errors of immunity (IEIs) are monogenic diseases of the immune system. Despite the increasing genetic advancements, the diagnosis of IEIs still lean on clinical diagnosis. Dermatological manifestations are observed in a large number of IEI patients and can lead to proper approach and prompt intervention. Methods This cross‐sectional study was carried out between 2018 and 2020 on IEIs at a Children's tertiary care center in Tehran, Iran. Demographic details and age at onset of symptoms of IEI were recorded. Results Overall, 212 patients were included. Cutaneous findings were reported in 95 (44.8%) patients, and 61 of 95 (64.2%) reported skin lesions as the first clinical presentation. Skin infection (69, 72.6%) was the most frequent cutaneous manifestation, followed by eczematous rash (24, 25%). Conclusions Skin manifestations are a common feature in IEI patients and are readily recognizable by healthcare providers. This study tried to provide information on prognostic consequences.